Intrinsically Synchronized Flexible Visuo‐Haptic Device Operated by Single External Electric Field. Issue 7 (23rd January 2023) - Lee, Gilwoon; Park, Chaeyong; Park, Doowon; Choi, Seungmoon; Jeong, Unyong
Abstract: Providing multisensory expression in a synchronized form helps human perception in human‐machine interfaces. Synchronized visuo‐haptic integration has been relatively less explored because the two expressions operate by different principles. This study demonstrates a flexible visuo‐haptic device that generates haptic sensation by electrovibration (EV) in conjunction with the synchronized optical expression by alternating‐current electroluminescence (ACEL). This study suggests material design and electric field modulation that are effective for both EV and electroluminescence (EL). Owing to the structural simplicity of the opto‐electrovibration (O‐EV) device, the EV and EL are intrinsically coupled under single electric field input. A curved O‐EV device simultaneously provides localized frictional tactile expression and localized luminescence on the touch screen. This study opens a simple material approach for multisensory expression that can be useful in soft haptic devices. Abstract : A flexible synchronized visuo‐haptic device is presented. The device is based on electrovibration for haptic expression and on alternating‐current electroluminescence for optical expression. The two expressions are intrinsically coupled by single electric field via electric field modulation.